Isagani Cruz and His Fiction: A Footnote to the “Deconstructive Effect of Feminist Materialism on the Newly-Discovered Cordillera Archives” - Cruz, Isidoro M. (Animo Repository, 2023)
A cursory reading of Isagani R. Cruz’s literary theory and criticism on one hand, and his fiction on the other, suggests a disparity between Cruz as a scholarly literary critic and Cruz as a fictionist of stories “for adults only”; however, a detail in one of his short stories in his book, Father Solo and Other Stories for Adults Only, arouses a critical suspicion that his fiction is actually cultural criticism masquerading as irreverent or obscene fiction, so that the critic and the fictionist are one. That detail is found in “Once upon a Time Some Years from Now,” where the narrator, a lover of President Cory Fernandez who lived more than two decades after former President Cory Aquino, speaks of a footnote he needed to complete for his paper on the “deconstructive effect of feminist materialism on the newly-discovered Cordillera archives.” Cruz’s fiction and feminist materialism enable us to see that the Filipina in the seeming seat of power, represented by Cory Fernandez of the 21st century, continues to be held in thrall by foreign domination, capitalism, patriarchy and politicking—so that despite the “gender barrier” breaking and high technology, the Filipino nation after the People Power Revolution is a continued mimicry of the Cordillera Archives of the 1900s: a disempowered people who are still colonial possessions “not ready to govern themselves.”